2020
DOI: 10.1002/ehf2.12958
|View full text |Cite
|
Sign up to set email alerts
|

Fatal lymphocytic cardiac damage in coronavirus disease 2019 (COVID‐19): autopsy reveals a ferroptosis signature

Abstract: Aims Cardiovascular complications, including myocarditis, are observed in coronavirus disease 2019 (COVID‐19). Major cardiac involvement is a potentially lethal feature in severe cases. We sought to describe the underlying pathophysiological mechanism in COVID‐19 lethal cardiogenic shock. Methods and results We report on a 48‐year‐old male COVID‐19 patient with cardiogenic shock; despite extracorporeal life support, dialysis, and massive pharmacological support, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 29 publications
2
95
0
2
Order By: Relevance
“…Another large study of 20 patients found 14 with acute DAD and foci of organization [ 28 ]. Studies of smaller cohorts have also found acute DAD with little to no organization [ 26 , 42 , 57 ]. Organizing DAD begins to show up a week to 10 days after symptom onset and rarely within a few days of symptoms which may be due to subclinical phase or rapid disease progression [ 22 , 25 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another large study of 20 patients found 14 with acute DAD and foci of organization [ 28 ]. Studies of smaller cohorts have also found acute DAD with little to no organization [ 26 , 42 , 57 ]. Organizing DAD begins to show up a week to 10 days after symptom onset and rarely within a few days of symptoms which may be due to subclinical phase or rapid disease progression [ 22 , 25 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several evidences also reveal the occurrence of significant lymphopenia in a large proportion of COVID-19 patients [2][3][4]49,62 . Recently, a ferroptosis signature was reported in a case report of COVID-19 patient (48-year-old, male), showing 4-HNE, a reactive breakdown product of the lipid peroxides or oxidized phosphatidylcholine was positive in myocardial tissue staining and in the proximal tubules of acute kidney injury, with decreased lymphocytes in the blood 63 . An in vitro study also showed SARS-CoV-2 suppressed GPX4, the brake of ferroptosis 43 .…”
Section: A Hypothesis On the Association Between Covid-19 And Ferroptmentioning
confidence: 97%
“…The autopsy report further proves that T-cell lymphocytes with a CD4:CD8 proportion of 1.7 infiltrated the interstitial myocardium. Hypertrophy in the myocardial fibre occurs–-iron-catalysed regulatory cell death induced by extreme peroxidation of fatty acids [ 44 ]. Myocardial interstitial macrophage infiltration spreads, and there is no clear concerning damage to myocardial cells containing the left and right ventricles [ 45 ].…”
Section: Introductionmentioning
confidence: 99%